AUTHORITY OF THE BOARD OF REGIONAL REPRESENTATIVES TO MONITOR AND EVALUATE THE DESIGN OF LOCAL REGULATIONS AND LOCAL REGULATIONS IN CONSTITUTIONAL PERSPECTIVE - Restu Gusti Monitasari; Danial Danial; Fatkhul Muin (JHR (Jurnal Hukum Replik), 2022)
The Regional Representative Council has 3 powers as regulated in Articles 22D, 23E and 23F of the 1945 Constitution of the Republic of Indonesia, namely the powers of Legislation, Consideration and Supervision. The authority of the Regional Representative Council is expanded and added in Law No. 2 of 2018 concerning the People's Consultative Assembly, the People's Representative Council, the Regional Representative Council, and the Regional People's Representative Council, namely in Article 249 paragraph (1) letter j related to the Monitoring and evaluation of the Draft Regional Regulations and Regional Regulations. Normative juridical research method with a statutory approach. The purpose of this research is to find out and analyze constitutionally and legal problems that arise regarding the new authority of the Regional Representative Council. Based on the 1945 Constitution of the Republic of Indonesia, the new authority of the Regional Representatives Council is in the opposite direction because it is not included in the meaning of the 3 powers of the Regional Representatives Council which is referred to as the 1945 Constitution of the Republic of Indonesia. Legal problems that arise over the authority of the House of Representatives The area is an indication of rivalry between institutions, namely the Ministry of Home Affairs, the Governor, the Supreme Court and the Regional Representatives Council itself, this can be seen juridically, namely in the 1945 Constitution of the Republic of Indonesia, Law No. 23 of 2014 concerning Regional Government, Constitutional Court Decision No.137/PUU -XIII/2015 and No. 56/PUU-XIV/2016.Keywords: Constitutional, The Regional Representative Council, Authority, Monitoring and Evaluation of Draft Regional Regulations and Regional Regulations